Sportwissenschaft - Mastnak W (Deutsche Zeitschrift für Sportmedizin)
Background: Overuse syndromes and overuse injuries are a rather frequent pathological phenomenon in sports and occupational domains. Despite the evident differences between sports techniques and occupational skills, similar motor patterns might cause comparable pathological risks, hence the reason for interdisciplinary approaches that link sports-medical and occupational-medical perspectives. The core intention of this paper aims at the adaptation and implementation of sports-based models for preventive purposes in occupational public health.Method: Comparative review using PubMed and Google Scholar search. Inductive reasoning. Results: Similar strain patterns in various sports and occupations entail comparable risks of overuse syndromes. Although sports involve higher musculoskeletal intensities, pathological states in athletes are quantitatively relatively moderate. Sports-medical principles such as physiologically balanced strength training, avoidance of overload, biomechanically and anatomically optimised motor-patterns, adequate warm up and cool down, and advanced body-awareness seem to be efficient preventive means. Comparative research allows us to distinguish four core issues and to construct a theoretical framework comprising complex motor demands, endurance strain, maximal muscular exertion, and psycho-motor reactivity.Discussion: Sports-based preventive measures are far from being a standard in occupational public health domains. Providing appropriate tools still needs medical and feasibility studies. Although still based on translational reasoning, the currentstudy explores possibilities of how to prevent work-related overuse syndromes. Successful implementation, however, also requires the public awareness of a systematic and balanced control of external and internal risk factors.KEY WORDS: Overuse Syndrome, Work-Related Overuse Injury, Occupational Medicine, Preventive Healthcare, Public Health